2019
DOI: 10.1002/tox.22824
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of hepatocyte growth factor gene overexpression against hydrogen peroxide‐induced apoptosis in mesenchymal stem cells

Abstract: Hepatocyte growth factor (HGF) has recently been reported to exhibit antioxidant and antiapoptotic effects. Therefore, we investigated the effect of overexpression of HGF gene in H2O2‐treated mesenchymal stem cells (MSCs). HGF‐overexpression increased the cell viability from 50% to 84%, decreased the population of apoptotic cells from 20% to 16%, and decreased the intracellular reactive oxygen species (ROS) levels from 127% to 100% in cells treated with H2O2. HGF suppression decreased the cell viability from 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…It is reported that apoptosis by transfected Crispr-HGF was induced in mesenchymal stem cells [13]. Our results indicated that transfection of Crispr-HGF induces apoptosis in a time-dependent manner in Huh7 and Hep3B cells.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…It is reported that apoptosis by transfected Crispr-HGF was induced in mesenchymal stem cells [13]. Our results indicated that transfection of Crispr-HGF induces apoptosis in a time-dependent manner in Huh7 and Hep3B cells.…”
Section: Discussionsupporting
confidence: 62%
“…The CRISPR/Cas9 system was discovered as an acquired immune system, and it was observed in bacteria and archaea [13]. In CRISPR/Cas9 system, invading external DNA is processed by Cas9 nuclease into small DNA fragments, which are then incorporated into CRISPR locus of host genomes as the spacers [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proven that oxidative and nitrosative stress, caused by excessive levels of reactive oxygen species (ROS) and reactive nitrogen species (RNS), are among the crucial culprits for the inefficacy and the high mortality rates of stem cells after transplantation (Valle-Prieto & Conget, 2010). Several molecules, pathways, and mechanisms are supposed to be actively involved in the reactive speciesrelated cell death; for example, ROS-induced autophagy (Liu et al, 2015), nitric oxide (NO)-induced inactivation of nuclear factor κB (NF-κB) signaling pathway (Nakaizumi et al, 2012), and ROSinduced activation of mitogen-activated protein kinase (MAPK or MAP kinase) subfamilies which are involved in a verity of cellular and subcellular processes, including transcription, cell proliferation, cell differentiation, apoptosis, and also autophagy (Choi, Lee, Lee, Park, & Nam, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…VEGF-B protects retinal cells against oxidative stress and rescues retinal degeneration by upregulating the antioxidative genes GPX1 and SOD1 (Arjunan et al, 2018). Hepatocyte growth factor protects mesenchymal stem cells against H 2 O 2 -induced apoptosis by decreasing the phosphorylation of extracellular signal-regulated kinases and p38 (Choi et al, 2019). In this study, the therapeutic effects of ACF on photoaging are likely due to an attenuation of oxidative stress levels, an improvement in fibroblast viability, stimulation of collagen synthesis, inhibition of apoptosis, and stimulation of blood vessel formation.…”
Section: Figure 12 |mentioning
confidence: 99%